Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1121/1.4817888
|View full text |Cite
|
Sign up to set email alerts
|

Fast acoustic streaming in standing waves: Generation of an additional outer streaming cell

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 22 publications
5
32
0
Order By: Relevance
“…It was shown indeed that the same flow behavior is to be expected if M ≪ 1, Re ac ≫ 1 and Sh ≪ 1 (where Re ac = 1 2 ( λ π δν ) 2 , Sh = δν R , λ being the acoustic wavelength). Both experimental and numerical configurations match these conditions (see Table 1 in [29]).…”
Section: Methods and Set-upmentioning
confidence: 62%
See 3 more Smart Citations
“…It was shown indeed that the same flow behavior is to be expected if M ≪ 1, Re ac ≫ 1 and Sh ≪ 1 (where Re ac = 1 2 ( λ π δν ) 2 , Sh = δν R , λ being the acoustic wavelength). Both experimental and numerical configurations match these conditions (see Table 1 in [29]).…”
Section: Methods and Set-upmentioning
confidence: 62%
“…Fig. 1(b) shows the distorted streaming pattern (result from the numerical simulation N 2 further described in this paper) in the fast streaming regime, when two new streaming cells are observed in the center of the guide, near the acoustic velocity antinode (z/L = 0) [19,28,29]. Several sources could potentially be responsible for this mutation of streaming pattern: thermal effects were considered [26], as well as nonlinear propagation [29] and it was concluded that inertial effects on acoustic streaming could be the main source [29].…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…[2][3][4][5][6][7] The studies of Sharpe et al 2 and of Thompson and Atchley 4 first allowed quantitative studies of streaming velocity in the core region on the basis of particle image velocimetry (PIV) or laser Doppler velocimetry (LDV) measurements in the case of slow streaming. Later, measurements of fast acoustic streaming have been reported in Thompson et al, 5 Moreau et al, 6 and Nabavi et al 7 More recently, Reyt et al 8 proposed a comparison between numerical and experimental results of fast acoustic streaming. In all available studies of fast streaming, 1,5-12 both experimental and numerical, the authors observed a deformation of the streaming pattern when the nonlinear Reynolds number is increased.…”
Section: Introductionmentioning
confidence: 95%